Respuesta :
We are said that a rectangle has been transformed into the one indicated in Figure 1 according to this rule:
[tex]R_0, \ 90^{\circ}[/tex]
We know that the center of rotation is origin and two rules are applied to rotate a point 90 degrees, namely:
1. Clockwise
In this case, the rule to transform a point is:
[tex](x,y) \rightarrow (y,-x)[/tex]
This rule was already applied to form the image, so all we need to do is to reverse the answer using this formula, therefore:
[tex]For \ Q(-3,4): \\ \\ (y,-x)=(-3,4) \\ \\ \therefore y=-3 \ and \ -x=4 \therefore x=-4 \\ \\ Thus, \ the \ point \ is: \\ \\ \boxed{Q(-4,-3)}[/tex]
2. Counterclockwise
Applying the same previous concept but with the new rules for this case:
[tex](x,y) \rightarrow (-y,x)[/tex]
By reversing the answer, we have:
[tex]For \ Q(-3,4): \\ \\ (-y,x)=(-3,4) \\ \\ \therefore -y=-3 \therefore y=3 \ and \ x=4 \\ \\ Thus, \ the \ point \ is: \\ \\ \boxed{Q(4,3)}[/tex]
[tex]R_0, \ 90^{\circ}[/tex]
We know that the center of rotation is origin and two rules are applied to rotate a point 90 degrees, namely:
1. Clockwise
In this case, the rule to transform a point is:
[tex](x,y) \rightarrow (y,-x)[/tex]
This rule was already applied to form the image, so all we need to do is to reverse the answer using this formula, therefore:
[tex]For \ Q(-3,4): \\ \\ (y,-x)=(-3,4) \\ \\ \therefore y=-3 \ and \ -x=4 \therefore x=-4 \\ \\ Thus, \ the \ point \ is: \\ \\ \boxed{Q(-4,-3)}[/tex]
2. Counterclockwise
Applying the same previous concept but with the new rules for this case:
[tex](x,y) \rightarrow (-y,x)[/tex]
By reversing the answer, we have:
[tex]For \ Q(-3,4): \\ \\ (-y,x)=(-3,4) \\ \\ \therefore -y=-3 \therefore y=3 \ and \ x=4 \\ \\ Thus, \ the \ point \ is: \\ \\ \boxed{Q(4,3)}[/tex]
![Ver imagen danielmaduroh](https://us-static.z-dn.net/files/d8e/7c78a4db2e87fe10dbc17a45b63d4232.jpg)
Answer:
[tex]Q(4,3)[/tex]
Step-by-step explanation:
One type of transformation is rotations, which are done counter-clockwise direction.
In this case, we have a rotation of 90° around the origin (0,0), that can be expressed as
[tex](x,y) \implies (-y,x)[/tex]
Which means a 90° rotation would be done by changing coordinates positions and inverting the sign of y-coordinate.
However, the problem is giving the transformed coordinates where [tex]Q'(-3,4)[/tex].
So, applying the rule described above, the original coordinate is [tex]Q(4,3)[/tex].